2003
DOI: 10.1081/clt-120019121
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxicity Associated with Intentional Ziprasidone and Bupropion Overdose#

Abstract: We present a case that underscores the potential cardiotoxicities of these medications. Ziprasidone and bupropion ingestion can be associated with cardiotoxicities that may require several days of aggressive cardiac monitoring and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 12 publications
2
15
0
1
Order By: Relevance
“…Some recommendations include withholding antipsychotic medication if the QTc is above 500 ms or discontinuing the medication if the QTc increases by Ͼ25% after administration. In a case study of overdose with ziprasidone, 2400 mg produced a QTc of 445 ms (34). Similar findings were reported in other cases.…”
Section: Newer Atypical Antipsychotic Agentssupporting
confidence: 80%
“…Some recommendations include withholding antipsychotic medication if the QTc is above 500 ms or discontinuing the medication if the QTc increases by Ͼ25% after administration. In a case study of overdose with ziprasidone, 2400 mg produced a QTc of 445 ms (34). Similar findings were reported in other cases.…”
Section: Newer Atypical Antipsychotic Agentssupporting
confidence: 80%
“…No bupropion levels in blood were reported, and limited toxicology studies did not include testing for bupropion or many other cardiotoxic agents. Biswas and colleagues described a 17-year-old boy who ingested ziprasidone, bupropion, clonazepam, and lorazepam (17). About 2.5 h after ingestion, what was apparently a run of ventricular tachycardia was treated successfully with lidocaine, and a QRS interval of 120 ms with normal sinus rhythm was subsequently noted on an EKG.…”
Section: Discussionmentioning
confidence: 98%
“…In a review of the medical literature from 1950 through 2008 using Ovid MEDLINE and 1969 through 2008 using BIOSIS, we were able to identify only nine reports, that were not poison center reviews, of pediatric exposures to ziprasidone that were either accidental ingestions or intentional overdoses [5][6][7]. Three separate poison center reviews, one being multi-center, included pediatric patients but provided very little information about the individual pediatric exposures [3,10,15].…”
Section: Discussionmentioning
confidence: 99%
“…None of the nine case reports or poison center reviews reported ziprasidone levels. Sedation was the most common clinical effect reported [3][4][5][6][7][8][9][10][11][12][13][14], but medical intervention was only required in one patient. This was a 17-year-old who also ingested buproprion, clonazepam, and lorazepam, so it is impossible to attribute his symptoms to ziprasidone only [3,14].…”
Section: Discussionmentioning
confidence: 99%